Impact of seed system interventions on food and nutrition security in low and middle-income countries: A scoping review - Nabuuma, Deborah; Reimers, Christine; Hoang, Ky The; Stomph, TjeerdJan; Swaans, Cornelis P.M.; Raneri, Jessica Evelyn (Elsevier, 2022)
The role of seed systems in nutrition of smallholder farmers has received little attention. This review mapped evidence of impact on nutrition, identifying themes from 43 studies as direct seed supply, improving seed access, and adoption of improved seed. Results had more positive than mixed/negative impacts on food security, household resilience, dietary quality, and diversity and/or nutrition status. Studies were skewed towards cereals and improved seed compared to other species and traditional/indigenous seed, and geared towards seed rather than the seed system. While most evaluated seed adoption and impact, few reported strategies for sustainable inclusion into farmer seed systems. Enabling factors contributing to positive nutrition impact included use of multi-component interventions and gender-sensitive and participatory approaches that consider the contexts.